A novel origin destination based transit supply index: Exploiting the opportunities with big transit data. (May 2021) - Hussain, Etikaf; Bhaskar, Ashish; Chung, Edward
Abstract: Quantifying transit resources and its networkwide temporal distribution is needed for the informed transit planning and operations decisions. One effective way to estimate the transit resource provision to a zone is to calculate the transit supply index. However, in literature, Supply Index (SI) is modelled considering the transit services allocated to a zone and ignores the quality and quantity of the supply provided between two zones. Addressing this need, this paper proposes a novel origin-destination based supply index (odSI) that incorporates a) zonal characteristics such as transit routes operate in origin zone, number of trips made by those routes, walk buffer areas of transit stops, and the total area of the zone; b) the quality of the service provided in terms of the average speed and route straightness ratio; and c) origin-destination dependent variables such as the minimum number of transfers needed to travel between two zones, the average transit speed between those zones, straightness of transit routes, and total available capacity. As proof of concept, the proposed odSI model is applied on the real network from Brisbane, Australia, at Statistical Area-2 level. The odSI results for 136 × 136 zonal pairs are presented for four different time periods (two peak and two off-peak periods). Furthermore, detailed analysis is carried for a zone, Grange, as an origin and the remaining 135 zones as destinations. The applicability of the proposed odSI model on Brisbane demonstrates its capability to provide valuable insights for an extensive network, which can help planners visualise and improve the complex and cumbersome networks in a more effective manner.